A Catholic ‘magician’ historicises ‘magic’: Éliphas Lévi’s Histoire de la Magie - Otto, Bernd-Christian (History and Religion, 2015)
One of the arguments made in the presentvolume is thatnarrativesofa‘reli-gious past’are inevitably construed and that they usuallyconceal this deficiencythrough various strategies. The use of an overlypersuasive tone–i. e. the narra-tor’sexhibition of a‘heavy form of confidence’(Ricoeur2003,58)–with the in-tention of supportingthe‘presumed“coherency”’(White 1978,103) of the re-spective narrative is suchastrategy, which is oftengrounded inamoreorlessnaïveidea of‘historicalrealism’.The present article intends to show that thesame applies,perhaps even more strongly,tonarrativesofa‘magic past’or,briefer, to‘magic historiography’.‘Magic historiography’appears to be evenmore problematic than‘religious historiography’as the precise nature of its sub-ject (‘magic’)isperpetuallydisputed, not onlyinscholarlyliterature¹butthroughout the entire conceptual history of‘magic’,which covers no less than2.500years oftextual sources (cf. Otto2011). In fact,‘magic historiography’isnot at allanovelgenre, butgoes back as far as,say,the beginning of book 30of Plinythe Elder’sNatural History,aremarkablyconstrued text that can beviewed as the prototype of one specific subgenre of‘magic historiography’,namely,polemical‘magic historiography’<br